Superior Mesenteric Artery Syndrome in a Patient with Cerebral Palsy. (26th June 2014) - Neuman, Adi; Desai, Bhavita; Glass, Daniel; Diab, Wassim
Abstract : Superior mesenteric artery syndrome involves compression of the third part of the duodenum due to narrowing of the area between the aorta and the superior mesenteric artery (SMA). We will describe the case of a 34-year-old with cerebral palsy who presented with abdominal pain, nausea, vomiting, and weight loss and was diagnosed with SMA syndrome via CT-imaging. With failure of conservative measures, our patient underwent a duodenojejunostomy after which improvement in her weight as well as relief of her abdominal symptoms was noted. Given the rarity of this syndrome, physicians need to keep a high index of suspicion in order to prevent the damaging consequences.